Dxpwkocpqwl,e-psol,;ce,s-plcwe'd,slpxos;w',]po
Answer:
- (x² + 2y² + 2xy)(x² + 2y² - 2xy)
Step-by-step explanation:
<h3>Given binomial:</h3>
x⁴ + 4y⁴
In order to factorize it, follow the steps:
<h3>Complete the square:</h3>
- x⁴ + 4y⁴ =
- (x²)² + 2*(x²)*(2y²) + (2y²)² - 2*(x²)*(2y²) =
- (x² + 2y²)² - (2xy)² =
- (x² + 2y² + 2xy)(x² + 2y² - 2xy)
Used identities:
- (a + b)² = a² + 2ab + b²
- a² - b² = (a + b)(a - b)
anna plis jangan tanya saya 1×7=7
Answer:
243 ft2
Step-by-step explanation:
9*3= 27
3*3= 9
27*9=243 ft2